Using kiosks as information-delivery channels to apply for Schemes and other government services for Rural India (International Journal of Engineering and Computer Science, 2017)
With the advent of Information Technology into almost every aspect of our lives, are we all really able to benefit fromit? This paper proposes a way to boost the success of government Schemes for Rural Development using kiosks. In the paper, asolution is discussed that addresses the problem of government schemes not reaching their full potential via awareness among eachand everyone, and attempts to resolve it by using kiosk machines, to supply information regarding government schemes. The mainpurpose is to provide information regarding government schemes to even those rural residents who can barely interact with anelectronic device. To do so, a very simple and easily understandable interface has been introduced in the paper. This interface mayalso provide audio/visual aid. Using this, a person may also get a token, using his/her aadhar card number, to meet with the respectiveoffice to proceed for a scheme. In the later versions, feature to transfer a particular page onto the persons mobile phone can also beadded.